Effects of maxillary expansion on hearing and voice function in non-cleft lip palate and cleft lip palate patients with transverse maxillary deficiency: a multicentric randomized controlled trial - Harpreet Singh; Raj Kumar Maurya; Poonam Sharma; Pranav Kapoor; Tanmay Mittal; Mansi Atri (Brazilian Journal of Otorhinolaryngology, 2021)
Introduction: The association between the treatment of transverse maxillary deﬁciency and the recovery of hearing and voice functions has gained attention in recent years. Objective: This prospective controlled trial aimed to evaluate the effects of rapid maxillary expansion on hearing and voice function in children with non-cleft lip palate and bilateral cleft lip palate with transverse maxillary deficiency Methods: 53 patients (26 non-cleft and 27 bilateral cleft lip palate; mean age, 11.1 ± 1.8 years) requiring rapid maxillary expansion for correction of narrow maxillary arches were recruited for this trial. Eight sub-groups were established based on the degree of hearing loss. Pure-tone audiometric and tympanometric records were taken for each subject at four different time periods. The first records were taken before rapid maxillary expansion (T0), the second after expansion (T1) (mean, 0.8 months), the third after three months (T2) (mean, 3 months) and the fourth at the end of retention period (T3) (mean, 6 months). ANOVA and Tukey HSD post-hoc tests were used for data analysis. Additionally, voice analysis was done using an updated PRAAT software program in a computerized speech lab at T0 and T2. A paired-samplet-test was used for comparisons of mean values of T0 and T2 voice parameters within both groups. Results: Rapid maxillary expansion treatment produced a significant increase in the hearing levels and middle ear volumes of all non-cleft and bilateral cleft lip palate patients with normal hearing levels and with mild conductive hearing loss, during the T0–T1, T1–T2, T0–T2, and T0–T3 observation periods (p < 0.05). The significant increase was observed in right middle ear volumes during the T0–T1, T0–T2 and T0–T3 periods in non-cleft patients with moderate hearing loss. For voice analysis, significant differences were observed only between the T0 and T2 mean fundamental frequency (F0) and jitter percentage (p < 0.05) in the non-cleft group. In the cleft group, no significant differences were observed for any voice parameter between the T0 and T2 periods. Conclusion: Correction of the palatal anatomy by rapid maxillary expansion therapy has a beneficial effect on both improvements in hearing and normal function of the middle ear in both non-cleft and bilateral cleft lip palate patients. Similarly, rapid maxillary expansion significantly influences voice quality in non-cleft patients, with no significant effect in BCLP patients.